Comparative Efficacy and Safety of Dopamine Agonists in Advanced Parkinson's Disease With Motor Fluctuations: A Systematic Review and Network Meta-Analysis of Double-Blind Randomized Controlled Trials - Ruan, Xinglin; Lin, Fabin; Wu, Dihang; Chen, Lina; Weng, Huidan; Yu, Jiao; Wang, Yingqing; Chen, Ying; Chen, Xiaochun; Ye, Qinyong; Meng, Fangang; Cai, Guoen (Frontiers in Neuroscience, 2021)
Abstract Background: Movement fluctuations are the main complication of Parkinson’s disease (PD) patients receiving long-term levodopa (L-dopa) treatment. We compared and ranked the efficacy and safety of dopamine agonists (DAs) with regard to motor fluctuations by using a Bayesian network meta-analysis (NMA) to quantify information from randomized controlled trials (RCTs). Methods and findings: We carried out a systematic review and meta-analysis and only RCTs comparing DAs for advanced PD were included. Electronic databases (PubMed, Embase, and Cochrane Library) were systematically searched for relevant studies published until January 2021. Two reviewers independently extracted individual study data and evaluated studies for risk of bias using the Cochrane Risk of Bias tool. Network meta-analyses using a Bayesian framework were used to calculate the related parameters. The prespecified primary and secondary outcomes were efficacy (‘ON’ time without troublesome dyskinesia, ‘OFF’ time, ‘ON’ time, ‘UPDRS-III’, and ‘UPDRS-II’) and safety (treatment-emergent adverse events (TEAE) and other adverse events) of DAs. The results are presented as the surface under the cumulative ranking (SUCRA) curve. A total of 20 RCTs assessing 6,560 patients were included. The general DA effects were ranked from high to low with respect to the amount of ‘ON’ time without troublesome dyskinesia as follows: apomorphine (SUCRA=97.08%), pramipexole_IR (probability=79.00%), and ropinirole_PR (SUCRA=63.92%). The general safety of DAs was ranked from high to low with respect to TEAE as follows: placebo (SUCRA=74.49%), pramipexole_ER (SUCRA=63.6%), sumanirole (SUCRA=54.07%), and rotigotine (SUCRA=53.84%). Conclusions: This network meta-analysis shows that apomorphine increased ‘ON’ time without troublesome dyskinesia and decreased ‘OFF’ time for advanced PD patients. The addition of pramipexole, ropinirole, or rotigotine to levodopa treatment in advanced PD patients with motor fluctuations increased ‘ON’ time without troublesome dyskinesia, improved the UPDRS III scores, and ultimately ameliorated the UPDRS II scores, thereby maximising its benefit. This NMA of pramipexole, ropinirole, and rotigotine represents an effective treatment option and has an acceptable safety profile in patients with advanced PD.